Pengaruh Profitabilitas, Tingkat Hutang dan Ukuran Perusahaan terhadap Tax Avoidance Perusahaan Pertambangan - Abdillah Arif Nasution; Renika Hasibuan; Hartono; Nuniek Yuniarti Ningsih Renggaala; Mega Arisia Dewi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the influence of profitability, debt levels and company size on tax avoidance. The sample in this research is mining companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The sample in this study used a purposive sampling method to obtain a sample of 23 mining companies. Testing in this research uses the SPSS (Statistical Product and Service Solution) analysis tool and data analysis in this research uses multiple linear regression analysis. The results of this research show that the profitability variable has no effect on tax avoidance, the level of debt has no effect on tax avoidance, company size has no effect on tax avoidance. The variables profitability, debt level and company size together have a significant effect on tax avoidance.